Continuous cane sugar inversion process using immobilized invertase - Koli, Aditya C; Gaikar, Vilas G (Journal of chemical technology and biotechnology (1986), 2017)
BACKGROUND Sugarcane juice is mostly used by industry for manufacturing sucrose and invert sugars. However, during enzymatic processing of raw sugarcane juice for an extended period of time, maintaining enzyme stability is a major bottleneck in food and agricultural industries. The present work reports use of invertase immobilized on glutaraldehyde crosslinked chitosan beads, for continuous inversion of sugarcane juice for an extended period of time. RESULTS Complete inversion of clarified sugarcane juice was obtained in a continuous process for 4 days at an optimized flow rate of 0.3 cm3 min−1 and at a room temperature of 303 K. Only 4% decrease was seen in inversion efficiency up to the 7th day. Adsorptive behaviour of invert sugars on chitosan in the column led to a delay in product equilibrium. The immobilized invertase exhibited the maximum rate of reaction at a sucrose concentration of 0.5 mol dm−3 showing good stability in the pH range 3.0 to 6.0 and temperature range 30 °C to 60 °C. CONCLUSIONS The covalent immobilization of invertase on chitosan beads enhanced enzyme stability and as a result, the enzyme became more resistant to denaturation during storage and reuse compared with the free enzyme. Thus, better conversion was obtained in the continuous inversion of sugarcane juice for extended periods of time. © 2016 Society of Chemical Industry